Primary failure of eruption (PFE): clinical and molecular genetics analysis - Stellzig-Eisenhauer, Angelika; Decker, Eva; Meyer-Marcotty, Philipp; Rau, Christiane; Fiebig, Britta S.; Kress, Wolfram; Saar, Kathrin; Rüschendorf, Franz; Hubner, Norbert; Grimm, Tiemo; Witt, Emil; Weber, Bernhard H. F. (Journal of orofacial orthopedics, 2010)
The term "primary failure of eruption" (PFE) refers to the complete or partial failure of a primary non-ankylosed tooth to erupt due to a disturbance of the eruption mechanism. Up to now, the molecular basis for this failure was unknown.